Smart Home Gardening System Powered by Solar - Mhd Halim, Nur Irdina Damia; Mohamed Ali, Riyaz Ahmad (Evolution in Electrical and Electronic Engineering, 2023)
Most plants need water to thrive and maintain their freshness. Therefore, this project outlines a method that individuals may implement in their daily lives nowadays, as gardening has become a highly popular activity at home due to Covid-19. Indirectly, users may care for as well as water the plants more efficiently even when the user is not thereby using a Smart Home Gardening System powered by Solar. With the aid of a moisture sensor and water pump, this system has been created as an automatic watering plant that can be switched on in line with the time specified by Blynk from the smartphone. There is also a feature for keeping track of the humidity and temperature of the area around the user's plant. As long as there is a Wi-Fi connection, the design uses a DHT11, soil moisture sensor, relay board, solar panel, NodeMCU, water irrigation, and water pump to operate the entire system. Based on the testing done during the day, the system will be in operation when the solar system detects sunlight and connects to the moisture sensor. The pump will turn on when the soil dries up, and water will be sent to the ground until it is moist. In contrast, there won't be any watering activity at night because the solar panel and pump will remain off. Additionally, a variety of factors such as the type of pump and the size of the tube from the water irrigation kit that was used, have an impact on how long it takes for the soil to get moist. Lastly, in conclusion, this project has successfully identified and built a system for gardening that has the function and ability to monitor the plants at home and self-irrigate the plants. In general, the system is functioning properly after a certain test.